2022
DOI: 10.1021/acs.cgd.2c00362
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystal Formation in l-Menthol/Phenol Eutectic System: Experimental Study and Thermodynamic Modeling

Abstract: Deep eutectic solvents (DESs) are eutectic mixtures containing a hydrogen-bond acceptor and donor, forming a mixture with a significantly lower melting temperature than those of its pure constituents. DESs containing cyclohexyl and phenolic alcohols draw particular attention due to the observed large depression in the melting temperature of the mixture. The present study investigates in detail the solid–liquid equilibria (SLE) in the l-menthol/phenol eutectic system. Differential scanning calorimetry and powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…The crystallization characteristics of the DESs were determined by cryogenic XRD testing on the three DESs. All DES crystal patterns showed a significant difference from their pure materials, confirming the formation of new crystalline phases (Figure G–I). Otherwise, the DES crystal patterns should be composed of a superposition of two pure materials’ diffraction peaks . This also showed that TBAC formed cocrystals with the three dihydric alcohols in a low-temperature state.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The crystallization characteristics of the DESs were determined by cryogenic XRD testing on the three DESs. All DES crystal patterns showed a significant difference from their pure materials, confirming the formation of new crystalline phases (Figure G–I). Otherwise, the DES crystal patterns should be composed of a superposition of two pure materials’ diffraction peaks . This also showed that TBAC formed cocrystals with the three dihydric alcohols in a low-temperature state.…”
Section: Resultsmentioning
confidence: 73%
“…However, the melting point change was not enough to prove that DES solidification formed cocrystals. The COSMO-RS approach that considered the most important modes of the molecular interactions could provide accurate and efficient screening of the conformers for co-crystallization. , Among these, the excess enthalpy (Δ H ex ) of a virtual supercooled liquid for the two-component mixture relative to the pure components could be regarded as the parameter to evaluate the tendency of those two compounds to form a cocrystal, where the more negative the Δ H ex value is, the more likely it is for the compounds to form cocrystals. Table summarizes the Δ H ex values for several common HBDs and the three dihydric alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…Second, three L-menthol-based eutectic systems containing alcohols, i.e., L-menthol/neopentyl alcohol, L-menthol/thymol, and L-menthol/phenol, are compared. L-menthol/thymol and L-menthol/phenol show strong negative deviations from the ideal behavior [ 53 , 54 ]. In contrast, L-menthol/neopentyl alcohol is an ideal eutectic system.…”
Section: Resultsmentioning
confidence: 99%
“…The melting enthalpy of a cocrystal represents the difference between the enthalpy of the cocrystal in the solid phase and the enthalpy of the liquid solution. In previous works, ,,,, we used the volume of the cocrystal unit cellestimated from powder X-ray diffraction (PXRD) measurementsand the volume of a pure constituent unit cell to confirm the stoichiometry of the cocrystal. Thus, the cocrystal represents a solid consisting of units of each constituent in the corresponding cocrystal stoichiometric ratio.…”
Section: Methodsmentioning
confidence: 99%
“…The activity coefficients of components in the liquid solution can be calculated using various thermodynamic models. Correlative activity coefficient models could accurately describe the nonideality of various eutectic systems with cocrystal formation. , In this work, we used the nonrandom two-liquid (NRTL) equation to calculate the activity coefficients of components as follows …”
Section: Methodsmentioning
confidence: 99%